Atmospheric River Precipitation Contributed to Rapid Increases in Surface Height of the West Antarctic Ice Sheet in 2019. Issue 5 (2nd March 2021) - Adusumilli, Susheel; A. Fish, Meredith; Fricker, Helen Amanda; Medley, Brooke
Abstract: Estimating the relative contributions of the atmospheric and dynamic components of ice‐sheet mass balance is critical for improving projections of future sea level rise. Existing estimates of changes in Antarctic ice‐sheet height, which can be used to infer changes in mass, are only accurate at multiyear time scales. However, NASA's Ice, Cloud, and land Elevation Satellite‐2 (ICESat‐2) laser altimetry mission now allows us to accurately measure changes in ice‐sheet height at subannual time scales. Here, we use ICESat‐2 data to estimate height changes over Antarctica between April 2019 and June 2020. These data show widespread increases in surface height over West Antarctica during the 2019 austral winter. Using climate reanalysis data, we show that 41% of increases in height during winter were from snow accumulation via extreme precipitation events—63% of these events were associated with landfalling atmospheric rivers (ARs) which occurred only 5.1% of the time. Plain Language Summary: Over a hundred gigatonnes of ice are being lost to the ocean from Antarctica each year, adding to ongoing sea level rise. Policymakers and stakeholders are interested in how much sea level rise will occur in the coming decades due to ice loss from Antarctica, but the range of values that scientists are providing is currently too large for efficient planning. One reason for this large range in predictions is the lack of data over the vast ice sheets. Satellites are the only way in which we can collect sufficient data to improve projections. In 2018, NASA launched a new satellite, ICESat–2, that is capable of accurately measuring changes in height over Antarctica. Using these data, we found large increases in height over the ice sheet in 2019. Using a computational model of the atmosphere and snow, we show that these height increases occurred due to increased snowfall. After evaluating the ability of the model to accurately represent ongoing changes, we used it to show that 41% of height changes due to winter snowfall over West Antarctica occurred because regions in the atmosphere where a lot of moisture is transported, called "atmospheric rivers", delivered large quantities of snow. Key Points: We show precise estimates of subannual height changes over the Antarctic Ice Sheet during 2019 using ICESat‐2 laser altimetry In West Antarctica, 41% of height increases in winter 2019 were due to several short‐duration extreme precipitation events In many cases, increases in surface height followed extreme precipitation from landfalling atmospheric rivers